Impact of delay in interval debulking surgery after neoadjuvant chemotherapy on survival in ovarian cancer - Khalil, Kheyal Azam; Habib, Maria; Usmani, Afshan Saeed; Shah, Muhammad Ansab; Anwer, Abdul Wahid; Syed, Aamir Ali (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the impact of delay between neoadjuvant chemotherapy and cytoreductive surgery on progression-free survival and overall survival in ovarian cancer cases. Method: The retrospective study was conducted at the Department of Surgical Oncology, Shaukat Khanum Memorial Cancer Hospital & Research Centre, Lahore, Pakistan, and comprised data from January 2019 to January 2022 of women diagnosed with stage III high-grade serous ovarian cancer who received neoadjuvant chemotherapy and underwent subsequent interval debulking surgery. The patients were divided into groups A and B based on time to surgery within 6 weeks and time to surgery more than 6 weeks, respectively. The endpoint was taken as progression-free survival and overall survival on follow-up. Data was analysed using SPSS 27. Results: Of the 2,100 patients who underwent surgery for ovarian cancer, 118(5.6%) women with mean age 52.18±9.3 years (range: 28-73 years) were included; 53(45%) in group A and 65(55%) in group B. Overall recurrence rate in this cohort was 76(64.4%); 36 (67.9%) in group A and 40 (61.5%) in group B. The mean progression free-survival was 15±1.5 months in group A and 18±2 months in group B (p=0.854). The mean overall survival across the sample was 44±1.8 months, and intergroup difference was not significant. (p=0.336). Conclusion: Delay in interval debulking surgery after neoadjuvant chemotherapy was not found to have a significant impact on progression-free survival and overall survival in ovarian cancer cases.